High accuracy system for the measurement of a directional antenna using an Arduino microcontroller - Khlf Ahmed, Riyadh; Hussein Kutheir, Khalid (International Journal of Engineering and Technology, 2019)
Telecommunication system based on sensors became part of our daily life. The development of two simple methods for high accuracy of antenna direction techniques is presented. Incremental encoder and endless potentiometer are sensing devices that convert the motion to electrical signal which can be read by some types of microcontroller devices. In our research article, two methods of transducers are suggested and implemented to provide feedback from the physical world. Electrical signals are generated by coupling the sensing device to the mechanical motor shaft. The accuracy of the first proposed setup depends on the number of pulses per revolution which is 0.351 degree per pulse. The accuracy of the second setup depends on range of input voltage reading by the microcontroller per revolution which is 0.072 degree per mv. According to our readings the second method has better accuracy than the first method. Highlights of these methods are the easy to installation, portability, cost effectiveness and better accuracy.
Keywords: Accuracy; Antenna; Microcontroller; Encoder.